Isolation of Rhodocyclus gelatinosus from poultry slaughterhouse wastewater - Ponsano,Elisa Helena Giglio (2002)
Four cultures of photosynthetic bacteria isolated from poultry slaughterhouse wastewater were identified as Rhodocyclus gelatinosus based on the following properties: reddish color of cultures in synthetic medium, presence of motility, slightly curved Gram-negative rods morphology, gelatin liquefying activity, utilization of citrate as carbon source and production of bacteriochlorophyl a and carotenoids of the spirilloxanthin alternative series. R. gelatinosus may represent a source of nutrients and pigments with application in poultry feed.